Nanostructured β‐tricalcium Phosphate (Ca3(PO4)2 Based Electrochemical Sensor for Detection of Methyl Parathion and Mercury (II) Ions - Sudhan, Narayanan; Sekar, Chinnathambi (Frontiers in Nanotechnology, 2021)
In this work, we have fabricated a new electrochemical sensor based on β-tricalcium phosphate (Ca3(PO4)2) nanoparticles (NPs) modified glassy carbon electrode (GCE) for the selective nonenzymatic determination of methyl parathion and mercury (II) ions independently. β-tricalcium phosphate (β-TCP) NPs were prepared by chemical precipitation method and structural and morphological properties were investigated by XRD, FTIR, and SEM. The electrochemical behavior of MP and mercury (Hg2+) ions were investigated by cyclic voltammetry (CV) and square wave voltammetry (SWV) techniques using β-TCP/GCE. The modified electrode exhibited excellent electrocatalytic activity towards both the MP and Hg over a wide linear range from 0.15 to 141 µM and 1 to 381 µM with the lowest detection limits of 88 and 136.4 nM respectively. The sensor has high selectivity towards MP and Hg in the presence of major interfering compounds such as 3-nitrophenol, 4-nitrophenol, 4-aminophenol, catechol, hydroquinone and heavy metals such as lead, cadmium and arsenic. Applicability of the fabricated sensor for detection of MP and Hg (II) ions has been tested in tap water by standard addition method.